THE EVOLUTION OF MATERNAL WELL-BEING: A JOURNEY THROUGH PREGNANCY'S PHYSIOLOGICAL, PHYSICAL, AND EMOTIONAL REALMS - kaya, Prof. Dr. Ayşe Nur; Yilmaz , Assoc. Prof. Dr. Mehmet Akif; Yildirim, Dr. Zeynep Sema (Global Journal of Medical and Health Science, 2024)
Pregnancy heralds a transformative journey for women, marked by profound physiological, physical, and emotional changes. While the prospect of pregnancy is generally viewed as exciting and desirable, the concurrent development of discomfort and symptoms can significantly impact women in various domains, guided by the evolving physiological, physical, and emotional landscape (De Haas et al., 2017). These changes intensify over time, exerting substantial effects on pregnant women's physical, mental, and social well-being. Notably, the enlargement of the uterus during pregnancy can impose limitations on movement and induce respiratory challenges due to pressure on the diaphragm (Shagana et al., 2018). Consequently, the health conditions of pregnant women undergo dynamic variations throughout the gestational period. This abstract delves into the multifaceted impact of pregnancy on women's health across the physical, mental, and social dimensions. Recognizing the intricate interplay of physiological, physical, and emotional changes, the narrative underscores the need for comprehensive evaluation by gynecologists, obstetricians, clinicians, and specialists. The assessment should be conducted at distinct trimesters, utilizing diverse evidence, precise measurement tools, and systematic observation methods to capture the nuanced evolution of health conditions throughout pregnancy.